Organization and Transcriptional Analysis of a Six-Gene Cluster around the rplK-rplA Operon of Corynebacterium glutamicum Encoding the Ribosomal Proteins L11 and L1 - Barreiro, Carlos (American Society for Microbiology, 2001)
A cluster of six genes, tRNA(Trp)-secE-nusG-rplK-rplA-pkwR, was cloned and sequenced from a Corynebacterium glutamicum cosmid library and shown to be contiguous in the C. glutamicum genome. These genes encode a tryptophanyl tRNA, the protein translocase component SecE, the antiterminator protein NusG, and the ribosomal proteins L11 and L1 in addition to PkwR, a putative regulatory protein of the LacI-GalR family. S1 nuclease mapping analysis revealed that nusG and rplK are expressed as separate transcriptional units and rplK and rplA are cotranscribed as a single mRNA. A 19-nucleotide inverted repeat that appears to correspond to a transcriptional terminator was located in the 3′ region downstream from nusG. Northern analysis with different probes confirmed the S1 mapping results and showed that the secE-rplA four-gene region gives rise to four transcripts. secE was transcribed as a 0.5-kb monocistronic mRNA, nusG formed two transcripts of 1.4 and 1.0 kb from different initiation sites, and the two ribosomal protein genes rplK and rplA were cotranscribed as a single mRNA of 1.6 kb. A consensus L1 protein binding sequence was identified in the leader region of the rplK-rplA transcript, suggesting that expression of the rplK-rplA cluster was regulated by autogenous regulation exerted by the L1 protein at the translation level. The promoters of the nusG and rplK-rplA genes were subcloned in a novel corynebacterial promoter-probe vector and shown to confer strong expression of the reporter gene.